Pediatric nursing secrets - Levasseur, Suzanne M. (Philadelphia, Pennsylvania : Hanley & Belfus, 2002)
Focused and concise, this text provides essential nursing care information about children from infancy through adolescence.
Child Development by Elaine M. Gustafson -- Physical Assessment of the Infant and Child by Barbara Hoyer Schaffner -- Parenting and Issues Related to Child Abuse by Bruce Wilson -- The Well Newborn by Rebecca L. Shabo -- The High-risk Newborn by Diana Odland Neal -- Breast-feeding by Patricia M. Murphy and Kathleen M. Moonan -- Respiratory System by Lauren R. Sorce, Andrea Kline and Joyce Weishaar -- Cardiovascular System by Deborah Bibeau
Includes bibliographical references and index.
Keywords: PEDIATRIC NURSING